(untitled) (LACCEI, 2024)
Wastewater pollution has been causing great concern throughout the world in recent decades since it seriously affects flora and fauna and transmits diseases such as typhoid fever, dysentery, cholera, among others. Therefore, in the present systematic review, natural flocculants and coagulants for the remediation of wastewater in South America were identified and compared, according to research journals published in scientific databases, in the last ten years. Information from scientific articles and academic theses belonging to the SciElo, Redalyc and Google Scholar databases was used considering the period 2012 - 2022 and the Spanish, English and Portuguese languages. 60 articles were identified, of which 10 that did not meet the research objective were discarded, reaching a total of 40 articles and 10 selected theses. A greater number of studies from Colombia was found, followed by Peru and Ecuador. One of the main limitations was the lack of command of the Portuguese language, since 4 articles written in that language were identified. Likewise, being South America the study area, limited articles related to flocculation and natural coagulation were found, of which 50 were selected for the present systematic review. As a result, the most effective species for the remediation of wastewater were identified. It is concluded that the most outstanding species Moringa oleifera "Moringa" and Opuntia ficus-indica "Tuna" present an efficacy for the remediation of wastewater in South America as flocculants and coagulants with an average removal percentage of 89.88% and 85.13%, respectively.